EFFECT OF NOVICE AND EXPERIENCED HEADTEACHERS WORK SANCTITY AND CONSEQUENT STUDENTS’ ACADEMIC ACHIEVEMENT - Farah Saeed (International Journal of Contemporary Issues in Social Sciences, 2024)
The role of head teachers is very important for the effectiveness of teachers working in the school. Head teachers’ role can significantly influence the students’ achievements. The study aims to find out the effect of novice and experienced head teachers work sanctity and consequent students’ academic achievement. To achieve its objectives, the study uses data of 32 schools collected from district Okara. Out of 32 schools, 22 schools were high schools and 10 schools were middle schools. From each school one head teacher and ten school teachers were selected using simple random sampling. Questionnaire was used as an Instrument to collect data from school heads and school teachers. Twenty-two head teachers from high schools and 10 head teachers from middle schools were selected to fill the questionnaires. Two hundred twenty school teachers from high schools and fifty teachers from middle schools were selected for the study. They were asked to respond to the questionnaire about their head teachers as they were novice and experienced. Data were entered to SPSS grid sheet, further data were screened and cleaned for analysis. In the light of research objectives and research questions, data were analyzed. Descriptive and inferential statistics were applied. To find the effect of novice and experienced head teacher independent samples t-test was conducted on each statement of the questionnaire, subscale and overall on scale. Pearson product moment coefficient of correlation was calculated to find out the relationship between head teachers work sanctity and student academic achievement. The results of the study will be elaborated in the paper.